Appeals to Interest : Language, Contestation, and the Shaping of Political Agency - Mathiowetz, Dean, 1972- (Book collections on Project MUSE., 2011)
"Explores the theoretical and political implications of self-interest within the context of neoliberal political, theoretical, and methodological imperatives"--Provided by publisher.